The losers club - Clements, Andrew, 1949-2019- (Random House, 2017)
Alec, a sixth-grade bookworm always in trouble for reading instead of listening and participating in class, starts a book club, solely to have a place to read, and discovers that real life, although messy, can be as exciting as the stories in his favoritebooks.